Kedudukan Hukum Objek Hak Atas Tanah Atas Perjanjian Pelepasan Hak Atas Tanah Yang Bayar Secara Cicilan - Sri Rumada Sihite (Pattimura Legal Journal)
Introduction: Agreement on the transfer of land rights number 04/L/GGPG/IX/2013 dated September 11, 2013 which became the issue raised by the author. The agreement made in the letter of agreement is a default between the parties who are considered to have owned the land, but it is interesting to see the legal position of the object of land rights on the agreement to release land rights which is paid in installments (study of the supreme court decision 2875/k/pdt/2016.